2023
DOI: 10.3390/s23042204
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Advanced Sensor Technologies for Non-Destructive Testing and Structural Health Monitoring

Abstract: This paper reviews recent advances in sensor technologies for non-destructive testing (NDT) and structural health monitoring (SHM) of civil structures. The article is motivated by the rapid developments in sensor technologies and data analytics leading to ever-advancing systems for assessing and monitoring structures. Conventional and advanced sensor technologies are systematically reviewed and evaluated in the context of providing input parameters for NDT and SHM systems and for their suitability to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 431 publications
(307 reference statements)
0
30
0
Order By: Relevance
“…Table 4. Typical EOCs and appropriate sensors for SHM systems [141]. Selecting the most appropriate sensor based on the system requirements and limitations depends on assessing specific sensor characteristics, such as (1) susceptibility to damage, (2) susceptibility to noise, (3) susceptibility to variations in the EOC, (4) susceptibility to chemical influences, (5) susceptibility to mechanical influences, (6) measurement accuracy, (7) error-proneness, and (8) cost.…”
Section: Sensing Technologiesmentioning
confidence: 99%
“…Table 4. Typical EOCs and appropriate sensors for SHM systems [141]. Selecting the most appropriate sensor based on the system requirements and limitations depends on assessing specific sensor characteristics, such as (1) susceptibility to damage, (2) susceptibility to noise, (3) susceptibility to variations in the EOC, (4) susceptibility to chemical influences, (5) susceptibility to mechanical influences, (6) measurement accuracy, (7) error-proneness, and (8) cost.…”
Section: Sensing Technologiesmentioning
confidence: 99%
“…Hence, acquiring an X-ray image of the exact same component at different source-to-detector distances (SDD) will yield varying intensity values. As the X-rays transmit through a part under test, the incident intensity is attenuated, as mathematically represented in equation (1).…”
Section: How Exposure Factors Affect Image Qualitymentioning
confidence: 99%
“…Non-Destructive Testing (NDT) involves a vast range of inspection methods used to assess the quality and integrity of materials, components, and structures without causing damage or compromising their functionality [1]. Through adequate application of NDT methods on components under test, flaws are detected and evaluated to ascertain if they constitute a defect that could impact a component's fitness-for-use [2].…”
Section: Introductionmentioning
confidence: 99%
“…Suitable SHM sensors are also used in other fields, such as construction progress monitoring, structural design, safety risk assessment, maintenance management, and smart operations. A comprehensive review of conventional sensor systems can be found in [ 6 ], and of advanced sensor systems in [ 7 , 8 ]. Data analysis: The recorded sensor data typically undergoes a process of data acquisition, signal conditioning, data transfer, data storage, signal processing, and data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable SHM sensors are also used in other fields, such as construction progress monitoring, structural design, safety risk assessment, maintenance management, and smart operations. A comprehensive review of conventional sensor systems can be found in [ 6 ], and of advanced sensor systems in [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%